A comparative performance analysis of carbonized briquettes and charcoal fuels in Kampala-urban, Uganda - Tumutegyereize, Peter; Mugenyi, Ronal; Ketlogetswe, Clever; Gandure, Jerekias (Energy for Sustainable Development, 2016)
As a result of the rising energy needs and environmental concerns, carbonized briquettes have been looked at as a possible substitute source of energy for charcoal in most of the developing regions. However their use and adoption in Uganda cannot be ratedamidst continued increase in charcoal demand fromthe ever growing urbanization. This study therefore investigated burning performance and cost in affecting briquette use. A comparative performance analysiswas carried out for locally purchased carbonized briquettes made frommatooke peels plus other household wastes and charcoal fuel denoted as A, B, C, and D, using a nested design. Calorific value, ash content, moisture content, burning time, and time of boil as well as cost per kilogram and per energy output, were the parameters compared. Results showed that gross calorific values were comparable for the two fuel types in the range of 4663–6517 kcal/kg. However, the average cost per energy output of briquettes as received was more than twice that of charcoal. This implies that briquettes are not worth their price since their calorific values are comparable to those of charcoal. The least expected was that shape and size of briquettes did not have influence on burning time and time of boil, an indication of briquette adulteration. Therefore further research needs to look at how the cost per energy output of briquettes can be reduced to be comparable to that of charcoal without compromising the quality. This workwill contribute to monitoring policies and promote efficient briquette production methods to reduce the cost of briquettes in order to create a competitive edge against charcoal. But at the moment, charcoal users may not be attracted to briquettes due to their high cost per energy output, calling for an alternative path of household waste utilization to provide sustainable energy.
Keywords: Performance analysis; Carbonized briquette; Charcoal; Nested design; Household waste; Monitoring policies